La patrimonialisation des produits du terroir à travers quelques musées consacrés au cognac et au vin en Nouvelle-Aquitaine - Florence Disson (In Situ)
The emergence of a new sensibility to heritage during the late eighteenth century was also the period, in France, which saw the creation of the country’s first museums. Food and gastronomy are being recognised today as heritage in their own right and several projects for Cités de la gastronomie, cultural centres devoted to gastronomy, are to be seen in different French cities. But older museums dealing with ‘produits du terroir’, local products, are probably the earliest to address the question of food. The study of a corpus of these cultural institutions allows us to examine their nature and their operation, in relation to society and in relation to local products. The names of the places seem to underline the latent uncertainty as to their status: places for maintaining traditions? places of production? ambassadors of local or national gastronomy? The history of these institutions is a reflection of how local products gradually came to be seen as expressions of a territorial identity and as a form of heritage. The diversity of the actors behind the creation of these institutions—local authorities, private individuals or associations—underlines the ambivalent status of these museums devoted to local products and the diversity of the sensibilities that surround this kind of heritage. They can be centred on the promotion of a particular agricultural activity, on the activity of a particular family or on preserving heritage. Closely connected with the notion of intangible cultural heritage, these museums of local products express the heritage designation of a particular food or drink as a component of a territorial identity, and the identification as heritage of specific gestures and savoir-faire.